Anti-sporozoite antibodies and immunity to malaria in a rural Gambian population. - Marsh, K; Hayes, R; Carson, D; Otoo, L; Shenton, F; Byass, P; Zavala, F; Greenwood, B (1988)
A conserved repeated epitope, (NANP)3, of the circumsporozoite protein of Plasmodium falciparum has been identified previously as a putative target for artificially induced immunity to malaria. We examined the role of humoral responses to this epitope in acquired immunity to malaria in a rural African population. Seropositivity to (NANP)3 was slow to develop (9% positive in subjects aged 1-11 years; 88% in those of 30 years and above), and responses in younger subjects were transient. The poor response in younger subjects did not appear to be due to immunosuppression by concomitant blood stage parasitization. The relationship between levels of anti-(NANP)3 antibodies and parasitaemia changed from positive to negative with age. 126 subjects age 1-11 years were followed through an entire transmission season; those who were seropositive at the beginning ended the season with lower parasite rates (20% vs 59%) and experienced fewer episodes of clinical malaria (0.43 vs 0.67). However, the trend towards increasing susceptibility to clinical malaria in subjects entering the transmission season with lower levels of anti-(NANP)3 antibodies was modest, and combined cross-sectional and longitudinal data indicated that the humoral response to (NANP)3 did not play a major role in the development of immunity to clinical malaria in the population we studied.